1989
DOI: 10.1590/s0034-71671989000100003
|View full text |Cite
|
Sign up to set email alerts
|

Necessidades psicossociais do menor de baixa renda, na faixa etária de 10 A 15 anos

Abstract: RESUMO -Este estudo visou apreender a problemâtica psicossocial de menores de 10 a 1 5 anos, a fim de obter dados que ampliem a capacitação operacional na ârea de Enferma gem em Saúde Mental Comunitâria junto à famnias de baixa renda. Pesquisa do tipo explo ratório, utilizando-se o método etnogrâfico combinado com a entrevista. Os resultados evi denciam a precariedade das condições sócio-econômicas em que vivem, a carência de afeto e a violência ffsica e moral com que são educados, etc ••• Suas doenças incidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Moreover, a number of studies have reported that poor infrastructure is characteristic for social vulnerability. Two studies point out that neighborhoods dominated by low social status presented hazardous life circumstances which included residences in a precarious state of repair and with insufficient rooms and thus hindering privacy, lack of piped water, sewage, and electricity as well as inadequate garbage collection ( 68 , 75 ). Poor infrastructure is also related to lack of public transportation, besides leisure, education and health centers ( 39 , 47 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, a number of studies have reported that poor infrastructure is characteristic for social vulnerability. Two studies point out that neighborhoods dominated by low social status presented hazardous life circumstances which included residences in a precarious state of repair and with insufficient rooms and thus hindering privacy, lack of piped water, sewage, and electricity as well as inadequate garbage collection ( 68 , 75 ). Poor infrastructure is also related to lack of public transportation, besides leisure, education and health centers ( 39 , 47 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported that socioeconomic adversities were associated with mental ill health ( 40 , 42 , 69 , 74 , 75 ). Less formal education and parental unemployment were found as strong predictors of high rates of mental disorders ( 40 , 50 , 71 , 72 , 74 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations